1991
DOI: 10.1007/bf00034676
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of water temperatures in chalk streams from air temperatures

Abstract: The water temperatures of four English chalk streams which have a large groundwater component in their discharge were studied. Simple linear regression models were used to described mean monthly water temperature as a function of mean monthly air temperature. There were no significant between-year differences within rivers, in the case of the Lambourn, Winterbourne and Tadnoll. For the Frome, only one year out of the eight studied was significantly different from the others. Further analysis revealed that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 19 publications
4
58
1
Order By: Relevance
“…Environmental parameters (dissolved oxygen: DO, conductivity, pH) were measured in the field using portable sensors. Air temperatures were used in this work since they are a strong predictor of water temperatures, particularly in shllow lakes [39,40]. The monitoring of this parameter is part of the National Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA).…”
Section: Samplingmentioning
confidence: 99%
“…Environmental parameters (dissolved oxygen: DO, conductivity, pH) were measured in the field using portable sensors. Air temperatures were used in this work since they are a strong predictor of water temperatures, particularly in shllow lakes [39,40]. The monitoring of this parameter is part of the National Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA).…”
Section: Samplingmentioning
confidence: 99%
“…We assume that previous meteorological states (e.g., air temperature, rainfall) influence the current water temperature [6][7][8][9][10][11][12][13]. Specifically, we assume that Y t is related to X t-k where Y t and X t-k are defined to be the hourly water temperature at hour t and meteorological variables at hour t-k, respectively.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…As shown in Fig. 9 There are a number of research work on water temperature prediction models such as statistical models and deterministic models [4][5][6][7][8][9][10][11][12][13]. These studies are usually aimed only at the achievement of higher prediction accuracies and basically carried out as theoretical research.…”
Section: Evaluation Of the Water Temperature Prediction Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Linear regression models have been used to estimate water temperature using only air temperature for mostly weekly and monthly data as the input parameter [18][19][20][21][22][23]. Studies have shown that as the time scale increases (daily, weekly, monthly, and annually), the model will be more accurate and reliable in estimating water temperatures [6,8,9,13,24].…”
Section: Introductionmentioning
confidence: 99%